The Conventional RT is Not Applicable for Testing the Acoustical Quality of Unroofed Theatres. Issue 1 (March 2013) - Mo, Fangshuo; Wang, Jiqing
The use of reverberation parameters (reverberation time and early decay time) was a question for reverberance evaluation of unroofed spaces such as traditional Chinese courtyard theatres or Greek/Roman amphitheatres, with the absence of large amount reflections from the top. Subjective reverberance comparison tests of synthetic listening signals in an unroofed space and an enclosed space which have approximately the same exponential decay rate were conducted in our laboratory. It demonstrated the perceived reverberance is also affected by their spatial aspects, which is noticeable in an unroofed space. Therefore, conventional reverberation parameters RT and EDT based on monophonic recording are not adequate for describing the acoustical quality in unroofed spaces as we usually do for enclosed spaces, and the factor of spatial information of the reflections should not be neglected for reverberance criteria.